The microbiome and metabolome analyses in monitoring pathogenic bacteria and antibiotic residues in sea cucumber stichopus ocellatus from pahang, malaysia - Choo Mei, Yen (2024)
Sea cucumbers, including Stichopus ocellatus, play an important role in maintaining the health and balance of the marine ecosystem. They also contribute to nutrient cycling and provide a source of food for many marine animals. They are highly valued as a delicacy in many Asian countries, leading to overfishing in some areas. Despite their ecological and economic importance, sea cucumbers are facing threats from overfishing, habitat destruction, and pollution. In recent years, anthropogenic driven marine pollution represents a global hazard that influences the ecology of marine ecosystems. Kuantan, being the capital of Pahang, generate tonnes of waste and garbage from human activities such as fishing, mining and recreational activities, which can cause pollution in coastal waters. On the other hand, there are not much development in Pekan. It is certain that the coastal ecosystem would be severely stressed by the release of pollutants and dangerous compounds from disposal wastes, which will have an influence on the diversity of the microbiota. Most sea cucumbers are usually scavengers in the ocean. Hence, their gut microbiome may provide insights to the ecosystem and shift in the environment. The true potential of S. ocellatus in terms of gut microbiome and metabolite content, is not fully known. Hence, the first objective was to investigate the microbial diversity in S. ocellatus and the sediment representing the environment. Our findings showed that Vibrio genera was predominant in Kuantan samples whereas Synechococcus E genera was predominant in Pekan samples. The pathogenic bacterium, Vibrio parahaemolyticus was also isolated from the gut of S. ocellatus. Next, we also profiled the antibiotics found in the gut of S. ocellatus and sediment using ultra-high performance liquid chromatography with quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS). There were 15 antibiotics profiled and amikacin were the most prevalent, followed by gentamicin and ampicillin. The last objective was to evaluate the genomic function of the isolated bacterium, V. parahaemolyticus. We found the antimicrobial resistance genes, tet(35) and blaCARB-33 which confer resistance to beta-lactam and tetracycline antibiotics. These findings provide valuable insights of the marine environment in Pahang through highthroughput sequencing. In conclusion, S. ocellatus is a host to a diverse bacterial species and screening of pathogenic microbes in sea cucumber should be considered in the sea cucumber trade or other biotechnology relevant processes.